Wind field study for UAV flight corridor in urban environments - Zeng, Yunxi (2019)
As our city becomes smart and intelligent, UAVs are going to be widely used in delivery, traffic monitoring and even man riding. However, due to variable wind direction all year round and complex terrains or architecture in urban environments, the flying UAVs are highly possible crashed by high winds, then they may hurt people and cause property damage. Thus, wind field study for UAV flight corridor could be significantly important.